Advertising and Pseudo-Culture: An Analysis of the Changing Portrayal of Women in Print Advertisements. (June 2018) - Yazdanparast, Atefeh; Naderi, Iman; Spears, Nancy; Fabrize, Robert O.
This study investigates the use of mass media, specifically advertising, in cultural transformation projects to weaken cultures and replace them with a crafted pseudo-culture. We rely on Adorno's theory of pseudo-culture to examine how political ideologies shape cultural transformation using mass-mediated ad images. Following a content analysis and a semiotic analysis of print advertisements over a period of 48 years, we identify five major themes underlying pseudo-culture formation and the advertising strategies implemented to support these themes. This work also identifies four major tools used in pseudo-culture formation and demonstrates how pseudo-cultures may be formed, promoted, and abolished.